PROJEK PENGUATAN PROFIL PELAJAR PANCASILA PADA SISWA DI SMP NEGERI 1 SINJAI - Aco Agus, Andi; Kasmawaati, Andi; Bahri, Nurul Izzah (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2024)
Abstract : This research ains to find out : (1) planning implementation and evaluation in implementing the project to form a pancasila student profile for student at SMP Negeri 1 Sinjai, (2) inhibiting factors in implementing the project to form a pancasila student profile for student at SMP Negeri 1 Sinjai. The type of research used in this research is descriptive research with a qualitative. Data collection techniques include observation, interviewsan documentation using research intruments in the forms of interview guides, recording equipment and documentation. Triangulation and member checking are used as procedures to check the validity of the data, as well as using data reduction, data presentation, and drawing conclusions as data analysis techniques. The research results show that (1) (a) planning the project to strengthen the profile of pancasila student at SMP Negeri 1 Sinjai goes through several tages, namely designing time allocation and dimensions forming a facilitator team, determining a theme, (b) implementation of the project to strengthen the profile of pancasila students at SMP Negeri 1 Sinjai is carried out in four ways, namely orientation, contextualizaton, action, reflection and follow-up, (c) evaluation of the project to strengthen the profile of pancasila students at SMP Negeri 1 Sinjai, namely evaluating the process during project implementation, (2) The inhibiting factor in implementing the project to strengthen the profile of pancasila student at SMP Negeri 1 Sinjai is the lack of teacher understanding regarding the project to strengthen the profile of pancasila students, the different characteristics of students.Keywords : Project, Pancasila student profileAbstrak : Penelitian ini bertujuan untuk mengetahui : (1) perencanaan, pelaksanaan, dan evaluasi dalam pelaksanaan projek penguatan profil pelajar pancasila pada siswa di SMP Negeri 1 Sinjai. (2) faktor penghambat dalam pelaksanaan projek penguatan profil pelajar pancasila pada siswa di SMP Negeri 1 Sinjai. Adapun jenis penelitian yang digunakan pada penelitian ini adalah jenis penelitian deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi dengan menggunakan instrument penelitian berupa pedoman wawancara, alat rekam dan dokumentasi. Adapun triagulasi dan member check digunakan sebagai prosedur pengecekan keabsahan data, dan penarikan kesimpulan sebagai teknik analisis data. Hasil penelitian menunjukkan bahwa (1), (a) perencanaan projek penguatan profil pelajar pancasila di SMP Negeri 1 Sinjai melalui beberapa tahapan yaitu merancang alokasi waktu dan dimensi, membentuk tim fasilitator, menentukan tema, (b) pelaksanaan projek penguatan profil pelajar pancasila di SMP Negeri 1 Sinjai dilakukan dengan empat alur yaitu orientasi, kontekstualisasi, aksi, refleksi dan tindak lanjut (c) evaluasi projek penguatan profil pelajar pancasila di SMP Negeri 1 Sinjai yaitu mengevaluasi proses selama pelaksanaan projek. (2) faktor penghambat dalam pelaksanaan projek penguatan profil pelajar pancasila di SMP Negeri 1 Sinjai yaitu kurangnya pemahaman guru terkait projek penguatan profil pelajar pancasila, karakteristik siswa yang berbeda-beda.Kata kunci : Projek, Profil Pelajar Pancasila